The Political Economy of India's Federal System and its Reform - M. Govinda Rao; Nirvikar Singh (University of California, Economics Department, 2004)
This article examines the nature of India's federal system, and recent and potential reforms in its structure and working. We summarize key federal institutions in India, focusing particularly on the mechanisms for Center-state transfers. These transfers are large, and are the major explicit method for dealing with inequalities across constituent units of the federation. We examine the evidence on how India's political economy has affected the practical workings of the transfer mechanisms. This is followed by a consideration of actual and possible reforms in India's federal institutions, including tax assignments and local government, and a discussion of how they might be implemented in a politically feasible manner.
Keywords: 330; intergovernmental transfers; economic reform; federalism; regional inequalities